Public sector transformation processes and internet public procurement : decision support systems - Pomazalová, Nataša (Information Science Reference, 2013)
"This book presents the methods, theories and practices involved in the growth and expansion of decision support systems as they relates to the public sector transformation process as well as internet public procurement"--Anotace vydavatele
Obsahuje bibliografie a rejstřík
Premier reference source--Obálka
Keywords: veřejný sektor; veřejná správa; elektronická veřejná správa; veřejné zakázky; podpora rozhodování; public sector; public administration; electronic government; public contracts; decision support; sborníky; papers of several authors